Associations of LRP5 Gene With Bone Mineral Density, Bone Turnover Markers, and Fractures in the Elderly With Osteoporosis - Wang, Qi-Fei; Bi, Hong-Sen; Qin, Ze-Lian; Wang, Pu; Nie, Fang-Fei; Zhang, Guang-Wu (Frontiers in Endocrinology, 2020)
Objective: The study aimed to explore the associations of rs4988300 and rs634008 in the low-density lipoprotein receptor–related protein 5 (LRP5) gene with bone mineral density (BMD), bone turnover markers (BTM), and fractures in elderly patients with osteoporosis (OP). Methods: Our study included 328 unrelated OP patients with or without fractures. Genomic DNA was extracted for genotyping. BTM levels were assessed by electrochemiluminescence (ECL). Dual-energy X-ray absorptiometry (DXA) was employed to measure BMD in the lumbar spine (LS) and proximal femur. Basic features between the OP and fracture groups were analyzed using the t test. The Chi-square test was performed to analyze the differences in allele and genotype frequencies. The associations of single-nucleotide polymorphisms (SNPs) with BMD and BTM in the subgroups were investigated by the analysis of covariance (ANCOVA) adjusted for confounding factors. Results: In both females and males, individuals with fractures exhibited higher BTM levels and lower BMD values than those with OP (P<0.05). The allele and genotype frequencies of rs4988300 in the subgroups were significantly different (P<0.05). In both females and males suffering from OP, participants with rs4988300 GG or rs634008 TT presented lower procollagen I N-terminal propeptide (PINP) levels (P<0.05). Women with OP carrying rs4988300 GG exhibited lower BMD values at FN and TH (P<0.05). In both females and males with fractures, individuals carrying rs4988300 GG genotype or rs634008 TT genotype exhibited lower PINP levels and BMD values at FN and TH than those with other genotypes (P<0.05). Conclusions: Rs4988300 and rs634008 polymorphisms in the LRP5 gene are associated with bone phenotypes in the elderly with OP or fractures.